Methods of studying pathological demand avoidance in children and adolescents: a scoping review - Haire, Lauren; Symonds, Jennifer; Senior, Joyce; D’Urso, Giulio (Frontiers in Education, 2024)
The construct of pathological demand avoidance (PDA) is relatively new and contested. Clinical reports indicate a population who obsessively resist everyday demands and have an extreme need for control. Children and adolescents who might experience PDA, and their families, struggle significantly in their daily lives, creating a need for more research into the phenomenon. To assist the developing research field, this scoping review focuses on the methodologies used to study PDA in children and adolescents. A systematic search of six databases and grey literature uncovered 57 unique records after duplicates were removed. 21 documents containing 22 studies were retained for analysis. Of the 22 studies, 21 were from the UK and one was from the Faroe Islands. There were 18 quantitative analyses and 11 qualitative analyses. Half of the studies were cross-sectional and quantitative and almost half used mixed methods. Samples were non-representative and studies often used comparison groups of children with and without PDA. Researcher's conceptualisations of PDA were coded into categories of emotional, socio-cognitive, and neurological differences. Studies of PDA focused mostly on PDA symptoms, mechanisms, and precipitants, with fewer studies of PDA origins and problems resulting from PDA or possible supports for individuals. The EDA-Q and the DISCO were the main measures used to identify PDA. Quantitative data were often analysed using inferential statistics, and qualitative data were analysed using thematic analysis, content analysis, and narrative summaries. Implications for future research are discussed.a Under diagnosis individual children are counted more than once.